COMPUTER GRAFOANALITIC KINEMATICAL ANALYSIS FOR FOUR-BAR LINKAGE MECHANISM (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
In this work, a methodology for calculating a class of lever mechanisms is proposed using a current software product for solving algebraic equations. They are adapted in the environment of the theory of mechanisms, where the main kinematic parameters of the articulated four-link mechanism are presented in graphical form. These parameters are linear and angular velocities and linear and angular accelerations. The work is related to the course in general and mechanical engineering at the Technical University - Gabrovo.